Existence of multiple positive solutions for a class of infinite-point singular p-Laplacian fractional differential equation with singular source terms - Guo, Limin; Zhao, Jingbo; Liao, Lianying; Liu, Lishan (Nonlinear Analysis: Modelling and Control, 2022)
Based on properties of Green’s function and by Avery–Peterson fixed point theorem, the existence of multiple positive solutions are obtained for singular p-Laplacian fractional differential equation with infinite-point boundary conditions, and an example is given to demonstrate the validity of our main results.
Keywords: fractional differential model; multiple positive solutions; Avery–Peterson fixed point theorem; singular problem